2015
DOI: 10.1103/physrevd.91.123527
|View full text |Cite
|
Sign up to set email alerts
|

Inflation in scale-invariant theories of gravity

Abstract: Thanks to the Planck Collaboration, we know the value of the scalar spectral index of primordial fluctuations with unprecedented precision. In addition, the joint analysis of the data from Planck, BICEP2, and KEK has further constrained the value of the tensor-to-scalar ratio r so that chaotic inflationary scenarios seem to be disfavored. Inspired by these results, we look for a model that yields a value of r that is larger than the one predicted by the Starobinsky model but is still within the new constraints… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…To begin with, it has been shown that the most likely form of fðRÞ, in the absence of matter, compatible with the measured spectral indices is f ∼ R 2−δ , with 0 < δ ≪ 1 [9]; see also [10]. Other studies showed that scale-invariant gravity with quantum corrections can reproduce inflation and spectral indices in line with current observations [11] in the absence of inflaton or any other kind of matter fluid. Quantum corrections in the context of inflation have been recently considered in various approaches; see, e.g., [12][13][14][15].…”
Section: Introductionsupporting
confidence: 56%
“…To begin with, it has been shown that the most likely form of fðRÞ, in the absence of matter, compatible with the measured spectral indices is f ∼ R 2−δ , with 0 < δ ≪ 1 [9]; see also [10]. Other studies showed that scale-invariant gravity with quantum corrections can reproduce inflation and spectral indices in line with current observations [11] in the absence of inflaton or any other kind of matter fluid. Quantum corrections in the context of inflation have been recently considered in various approaches; see, e.g., [12][13][14][15].…”
Section: Introductionsupporting
confidence: 56%
“…Various descriptions of inflationary models in terms of scalar field models [53] and perfect fluid as well as F (R) gravity [54] have been examined. Moreover, the effects of quantum corrections on inflation have been explored in References [55][56][57]. We note that the BICEP2 experiment has recently detected the B-mode polarization of the cosmic microwave background (CMB) radiation with the tensor to scalar ratio r = 0.20…”
Section: Extension Of the Starobinsky Inflation Modelmentioning
confidence: 99%
“…k 2 ∼ R (see also [41]). In a recent investigation a similar approach has been successfully applied to study the quantum gravity modifications of the Starobinsky model [42] (see also [43][44][45][46][47][48] for other examples of quantum deformed quadratic gravity inflationary models).…”
Section: Introductionmentioning
confidence: 99%